A single-institution analysis of the utility of pre-induction ejection fraction measurement in patients newly diagnosed with acute myeloid leukemia. Issue 1 (January 2015) - Bryant, Adam; Sheppard, Dawn; Sabloff, Mitchell; Delbaere, Michelle; Maze, Ronnen; Allan, David; Atkins, Harold; Bence-Bruckler, Isabelle; Faught, Carolyn; Huebsch, Lothar; Tay, Jason; Zanke, Brent; et al.
Abstract Anthracyclines, a standard component of induction therapy for acute myeloid leukemia (AML) are known to be cardiotoxic. Existing evidence supporting routine baseline pre-induction cardiac function testing is limited. We conducted a retrospective analysis of 119 consecutive patients diagnosed with AML at our center from 2009 to 2012. In the 76 patients for whom induction chemotherapy was planned, baseline ejection fraction measurements were rarely abnormal (four cases), and in none of these abnormal cases did the result change management decisions. Awaiting LVEF evaluation results led to a delay in chemotherapy administration by a mean of approximately 2 days at significant additional costs to the healthcare system. Routine baseline ejection fraction measurement should be abandoned as it does not change management, results in treatment delay and unnecessary healthcare expenditures. More selective baseline testing, preferentially in patients in whom there is a clinical reason of cardiac disease, should be pursued.